Perancangan Human Machine Interface (HMI) Pada Modul Praktikum Sistem HMI Berbasis PLC Omron CP1E NA20DRA - Eggy Depto Maniar; Sigit Kurniawan; Maizal Isnen; Ahmad Ridwan (Jurnal Elektronika Listrik dan Teknologi Informasi Terapan, 2021)
This study aims to design practical learning media. The Human Machine Interface (HMI) learning module consists of a monitor to display control menus, PLC devices, and input-output devices. The design of the exemplary HMI display is needed to provide the required information to the user. The research method used in this study uses experimental methods and program design on the trainer module. From the study results, it can conclude that the use of the Omron CP1E NA20DRA PLC-Based HMI system is effortless to use as a learning medium and can train students in improving PLC programming skills.